B cell abnormalities in systemic lupus erythematosus - Grammer, Amrie C (BioMed Central, 2003)
Systemic lupus erythematosus (SLE) is a chronic, multisystem autoimmune disease characterized by the differentiation of short- and long-lived immunoglobulin secreting plasma cells that secrete pathogenic autoantibodies. Ectopic germinal centers and plasma cells secreting autoantibodies have been observed in lupus nephritis kidneys. Candidate genetic susceptibility loci for SLE include genes that affect differentiation and survival of plasma cells, such as those that influence activation, proliferation, cytokine and chemokine secretion/responsiveness, and apoptosis of the T and B cells that are involved in humoral immunity generated in germinal centers, as well as genes that are involved in presentation and clearance of apoptotic material and autoantigens by antigen presenting cells and other phagocytes. Emerging data have demonstrated that B lymphocytes are active participants in humoral immune responses that lead to T-dependent and T-independent differentiation of immunoglobulin-secreting plasma cells by homotypic CD154–CD40 interactions as well as continued stimulation by B cell activating factor through B cell maturation antigen, B cell activating factor receptor and transmembrane activater.